Dermatoglyphic Analysis of Asthma Sufferers in a Population Of Students At The Faculty of Mathematics and Science, Universitas Negeri Padang - Velina Salsabil; Afifatul Achyar; Yuni Ahda (Tropical Genetics, 2022)
Asthma is a disease defined as chronic inflammation of the airways which is characterized by recurrent coughing and shortness of breath. Dermatoglyphs are the appearance of tendrils and tendril patterns on the fingers, palms, toes and soles. Dermatoglyph is used as an aid in the detection of a number of diseases that have a strong heritable basis and is also used to detect abnormalities. This study aims to analyze and compare the patterns of dermatoglyphics in asthma sufferers and non-asthmatics on the fingertips. This type of research is descriptive research with cross sectional sampling method. Samples were taken from the student population of the Faculty of Mathematics and Natural Sciences, Padang State University as many as 100 samples of fingerprint patterns. The results obtained showed that there was a significant difference in the number of arch fingerprint patterns of asthmatics compared to normal individuals. Seeing this significant difference in numbers indicates a possible link between fingerprint patterns and asthma phenotypes.